2022
DOI: 10.1007/s11756-021-00988-3
|View full text |Cite
|
Sign up to set email alerts
|

Soil biotic and abiotic traits as driven factors for site quality of Araucaria angustifolia plantations

Abstract: Purpose: The role of soil biotic and abiotic factors in crucial ecosystem services such as primary production, organic matter dynamics, nutrient cycling, and soil biota community structure in the Araucaria ecosystem remains poorly quanti ed. We aimed to understand how the site quality affects the development of organic horizons, root growth, soil chemical properties, and the entire soil biota community in even aged and monospeci c Araucaria angustifolia plantations.Methods: We collected soil monoliths to descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…The soil fertility in such conditions was influenced by management practices that created different pathways into the soil ecosystem, as we had found in our PCA analysis. It agrees with the investigations performed by Six et al [ 20 ] and Souza et al [ 15 ] that reported a positive correlation between soil organic matter compartments and soil P content in natural ecosystems, and positive influences on soil fertility as affected by soil management, as we observed in this study for the Amazon Rainforest, and all fruticulture systems, respectively [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The soil fertility in such conditions was influenced by management practices that created different pathways into the soil ecosystem, as we had found in our PCA analysis. It agrees with the investigations performed by Six et al [ 20 ] and Souza et al [ 15 ] that reported a positive correlation between soil organic matter compartments and soil P content in natural ecosystems, and positive influences on soil fertility as affected by soil management, as we observed in this study for the Amazon Rainforest, and all fruticulture systems, respectively [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…In soil from Brazil’s Legal Amazon, the soil organic matter compartments are modulated by plant community composition. According to Souza et al [ 1 , 15 ] plant community with the following characteristics: (i) high diversity; (ii) with nitrogen fixers; (iii) high soil reaction in the rhizosphere by the extrusion of H + ; and (iv) high biomass production may enhance resource availability and improve both soil traits and soil organic matter compartments. However, in the fruticulture systems as land use, we lost all of these four characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of soil quality remains far from being understood, primarily because of a wide range of soil functions, and the different interactions among soil compartments. We also must take in consideration the lack of scienti c studies gathering dataset from long-term eld experiments considering the interaction of organisms, litter, and soil as in uenced by soil quality degrees (Souza et al 2022a). Soil compartments, such as: (i) litter that may be characterized by litter deposition (kg m − 2 ) and k-factor (years − 1 ) assess the input of organic matter, and the nutrient cycling process; (ii) soil -solid phase may be characterized by the chemical properties that determines the soil fertility and the soil capacity to sustain high biomass production; and (iii) soil organisms' community composition that may be characterized by the abundance of insects, arachnids, myriapods, etc.…”
Section: Introductionmentioning
confidence: 99%